Dukungan Emosional Teman Sebaya dengan Resiliensi dan Keterampilan Pengambilan Keputusan Pada Mahasiswa Broken Home di Yogyakarta - Triansyah, Khusnul Fera; Sumiyarini, Retno (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Jenderal Achmad Yani Yogyakarta, 2024)
Background: A broken home can be interpreted as a breakdown in the family which causes conflict, arguments, and divorce. A broken home due to parents’ divorce can affect children namely losing the purpose to live and life objective, causing a non-resilient personality and unconfident. Thus, children have difficulty identifying problems which affect their ability to make decisions in daily life. Hence, social support is needed. One of them is from peers. Objective: To learn the association between peers’ emotional support with resilience and the ability to make decisions in broken home students from divorced families. Method: The research is quantitative with a cross-sectional approach. The respondents were 102 broken home students due to their parents’ divorce aged 18 -25 years old who study in Yogyakarta in a 3-year diploma and undergraduate program. The instruments used were peers' emotional support, the Connor Davidson Resilience Scale (CD-RISC) dan the assessment of career decision-making (ACDM). Result: The result of the Somers statistic test showed a p-value of 0,003 (<0,05) which revealed the significant association between peer emotional support with resilience and a correlation coefficient value of 0,224. This illustrated a low closeness value and p-value of 0,489 (0,05) which demonstrated that there was no significant association between peer emotional support and the ability for decision-making. Conclusion: There is a significant association between peer emotional support and the ability for decision-making in broken home students due to parents' divorce in Yogyakarta.